2017
DOI: 10.1016/j.neuropharm.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The kynurenine pathway and the brain: Challenges, controversies and promises

Abstract: Research on the neurobiology of the kynurenine pathway has suffered years of relative obscurity because tryptophan degradation, and its involvement in both physiology and major brain diseases, was viewed almost exclusively through the lens of the well-established metabolite serotonin. With increasing recognition that kynurenine and its metabolites can affect and even control a variety of classic neurotransmitter systems directly and indirectly, interest is expanding rapidly. Moreover, kynurenine pathway metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
270
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(277 citation statements)
references
References 184 publications
(205 reference statements)
3
270
2
2
Order By: Relevance
“…However, this notion is based on in vitro analysis of cellular responses to LPS or cytokine administration (Corona, et al 2010; Guillemin, et al 2003) (Chiarugi, et al 2001; Schwarcz and Stone 2017). Consistent with a recent report (Liu, et al 2017), we also observed activation of microglia in the hippocampus in response to SNI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this notion is based on in vitro analysis of cellular responses to LPS or cytokine administration (Corona, et al 2010; Guillemin, et al 2003) (Chiarugi, et al 2001; Schwarcz and Stone 2017). Consistent with a recent report (Liu, et al 2017), we also observed activation of microglia in the hippocampus in response to SNI.…”
Section: Discussionmentioning
confidence: 99%
“…IDO1 initiates the metabolism of tryptophan into kynurenine (KYN). Kynurenine can be further converted to 3-hydroxy-kynurenine (3-HK) by kynurenine 3-monooxygenase (KMO), and ultimately transformed into quinolinic acid (QA) by kynureninase (KYNU) and 3-hydroxyanthralinic acid dioxygenase (HAAO) (Schwarcz and Stone 2017). Quinolinic acid is a neurotoxic N-methyl-D-aspartate receptor (NMDAR) agonist (Guillemin 2012; Santamaria and Rios 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The kynurenine pathway is relatively less understood despite its dominant role in tryptophan catabolism. This pathway has been studied mainly in biochemistry and neurology, in the latter case as a source of catabolites contributing to psychogenic disease (Schwarcz, Stone, 2017). Biochemically, IDO and TDO control the rate-limiting first step in tryptophan catabolism leading to generation of the key enzyme co-factor nicotinamine adenine dinucleotide (NAD).…”
Section: Introductionmentioning
confidence: 99%
“…Historical studies of the kynurenine pathway of tryptophan catabolism have defined roles in neurological and immunological functions [79]. IDO1 is extrahepatic and inducible in many cell types by interferons and other diverse pro-inflammatory signals.…”
Section: Ido1 Modifies Inflammation and Immunitymentioning
confidence: 99%